PENGARUH BIBIT KAKAO (Theobroma cacao L.) KLON Bl-50 TERHADAP ABU BOILER SAWIT DAN KOMPOS PAITAN (Thitonia diversivolia) - Nico Andri Siahaan; Tengku Edy Sabli (DINAMIKA PERTANIAN, 2025)
This research aims to determine the main and interaction effects of boiler ash and paitan compost (Tithonia diversifolia) treatment on the growth of cocoa seedlings (Theobroma cacao L.) clone BI-50. The research was conducted at the Experimental Garden of the Faculty of Agriculture, Riau Islamic University, in Pekanbaru City, from June to October 2023. The study used a completely randomized factorial design consisting of two factors. The first factor is the boiler ash dose (A), with four levels: 0, 100, 200, and 300 g per polybag. The second factor is the dosage of paitan compost (K), with five levels: 0, 20, 40, 60, and 80 g per polybag. The parameters observed were plant height, number of leaves, stem diameter, total leaf width, root volume, and root length. The data were analyzed statistically, and the BNJ test was performed at the 5% level. The results showed that the interaction between boiler ash and paitan compost was significant for plant height, number of leaves, stem diameter, root volume, and root length. The best treatment was 300 g boiler ash per polybag and 80 g paitan compost per polybag. The main effect of boiler ash was significant for all observation parameters. The best treatment was 300 g per polybag. The main effect of paitan compost was significant for all observation parameters. The best treatment was 80 g per polybag.